Optimizing educational management through the flipped classroom method: An innovation in Islamic education learning in the digital era - Atabik, Atabik; Fian, Khafifatul; Hardoyono, Fajar; Dahlan, Ahmad (Jurnal Cakrawala Pendidikan, 2025)
This experimental study employed nonequivalent control group design to examine the effect of the flipped classroom method on students’ achievement in Islamic education learning among grade XII students at SMA Negeri 1 Sumpiuh in 2024. The flipped classroom method was implemented by instructing students to study the material independently through learning videos followed by elaboration and discussion through online platforms. For data analysis, tests were administered to 30 students in the experimental groupand 30 students in the control groups. The results of the N-gain Score calculation showed that the improvement in material comprehension among students in the experimental group was higher than that of the control group. The N-gain score for the experimental group students was 0.3562, while that for the control group was 0.1511. Statistical analysis using an independent samples t-test showed that the comprehension ability of the experimental group was significantly higher than that of the control group (p > 0.05). Based on these findings, the flipped classroom method can be considered an effective alternative strategy to enhance students’ understanding of learning materials in online Islamic education.